2016
DOI: 10.1080/02670836.2015.1114310
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of laser-cladded Ni-based amorphous composite coatings

Abstract: A (Ni0.6Fe0.4)65B18Si10Nb4C3 amorphous composite coating has been fabricated on a mild steel substrate by a laser cladding process under different heat inputs. Observation of the structure and phase showed that the thickness of the coating decreased and the amorphous fraction increased when the laser cladding heat input was lower. The cooling rate increases when the heat input decreases, which favours the formation of amorphous phase. Microhardness and wear resistance test results indicated that a lower heat i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…So far, some technologies, such as cathodic arc vapor deposition (CAVD) [ 10 ], magnetron sputtering [ 11 ], and laser cladding [ 12 , 13 ] have been employed to deposit HEA coatings. However, some drawbacks restrict the application of these technologies, such as the high cost and low deposition efficiency for magnetron sputtering, and the high residual stress and high dilution for laser cladding [ 14 , 15 ]. Since it is different from the above technologies, atmospheric plasma spraying (APS) is an appropriate technology for depositing HEA coatings, as those drawbacks can be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…So far, some technologies, such as cathodic arc vapor deposition (CAVD) [ 10 ], magnetron sputtering [ 11 ], and laser cladding [ 12 , 13 ] have been employed to deposit HEA coatings. However, some drawbacks restrict the application of these technologies, such as the high cost and low deposition efficiency for magnetron sputtering, and the high residual stress and high dilution for laser cladding [ 14 , 15 ]. Since it is different from the above technologies, atmospheric plasma spraying (APS) is an appropriate technology for depositing HEA coatings, as those drawbacks can be overcome.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, increasing scanning speeds is theoretically favorable to the formation of an amorphous structure. Jin et al [30] experimentally demonstrated that a higher scanning speed favored the formation of an amorphous phase in their work. However, the results in this study showed the opposite to the above deduction, where an amorphous microstructure tended to form at relatively lower scanning speed (6 mm/s) while dendrites formed at a higher speed (10 mm/s).…”
Section: Resultsmentioning
confidence: 99%
“…Due to their outstanding properties (e.g., high strength, sufficient hardness, and excellent wear resistance) [2][3][4][5][6], HEAs are a kind of promising coating materials used in harsh environments, especially at high temperature. So far, most of the HEA coatings have been prepared by electrochemical deposition [7], magnetron sputtering [8,9], and laser cladding [10,11]. However, the preparation and industrial application of HEA coatings are limited owing to the low deposition efficiency, high residual stress, high dilution, and high cost of these techniques.…”
Section: Introductionmentioning
confidence: 99%